IMPORTANCE OF MODERN TECHNOLOGIES IN TEACHING EASTERN LANGUAGES - Saidnazarova Nodira Otaxon qizi (Western European Studies, 2024)
In recent years, the integration of modern technologies to facilitate the process of language teaching has changed the way of teaching and learning Eastern languages. Language learning applications, online platforms, virtual simulations, and interactive multimedia technologies have facilitated the language learning process. In this article, the importance of modern technologies in teaching oriental languages and their positive effects on the language learning process, learning oriental languages by integrating digital technologies and innovative technologies, and information on facilitating the teaching and language learning process is given
Keywords: language; eastern languages; communication; information technologies